Effect of renin-angiotensin-aldosterone system inhibitors on survival outcomes in cancer patients treated with immune checkpoint inhibitors: a systematic review and meta-analysis - Shen, Jinhai; Hou, Hui; Liang, Bowen; Guo, Xiao; Chen, Li; Yang, Yong; Wang, Yun (Frontiers in Immunology, 2023)
Background: Effect of renin-angiotensin-aldosterone system inhibitors (RAASIs) in combination with immune checkpoint inhibitors (ICIs) on prognoses in cancer patients remains controversial. This study systematically evaluated the effect of RAASIs on survival outcomes in cancer patients receiving ICIs treatment and provided an evidence-based reference for the rational use of RAASIs and ICIs combination therapy in clinical practice. Methods: Studies evaluating the prognoses of RAASIs-used versus RAASIs-free in cancer patients receiving ICIs treatment from inception to 1 November 2022 were retrieved by searching PubMed, Cochrane Library, Web of Science, Embase, and major conference proceedings. Studies in English reporting hazard ratios (HRs) with 95% confidence intervals (CIs) for overall survival (OS) and/or progress-free survival (PFS) were included. Statistical analyses were conducted using the software Stata 17.0. Results: A total of 12 studies containing 11739 patients were included, comprising ~4861 patients in the RAASIs-used and ICIs-treated group and ~6878 patients in RAASIs-free and ICIs-treated group. The pooled HR was 0.85 (95%CI, 0.75–0.96; P = 0.009) for OS and 0.91 (95%CI, 0.76–1.09; P = 0.296) for PFS, indicating a positive effect of RAASIs concomitant with ICIs in cancer patients. This effect was observed especially in patients with urothelial carcinoma (HR, 0.53; 95%CI, 0.31-0.89; P = 0.018) and renal cell carcinoma (HR, 0.56; 95%CI, 0.37-0.84; P = 0.005) on OS. Conclusions: Concomitant use of RAASIs and ICIs enhanced the efficacy of ICIs and this combination regimen was associated with significantly improved OS and a trend towards better PFS. RAASIs can be considered as adjuvant drugs when hypertensive patients receive ICIs treatment. Our results provide an evidence-based reference for the rational use of the RAASIs and ICIs combination therapy to improve the efficacy of ICIs and a strategy to relieve the heavy financial burden of cancer treatment.